Association of Postoperative Topical Prostaglandin Analog or Beta-Blocker Use and Incidence of Pseudophakic Cystoid Macular Edema. Issue 5 (May 2018) - Wendel, Colten; Zakrzewski, Helena; Carleton, Bruce; Etminan, Mahyar; Mikelberg, Frederick S.
Abstract : Purpose: The purpose of this article is to determine the association of postoperative topical prostaglandin analog (PGA) or topical beta-blocker use and the incidence of pseudophakic cystoid macular edema (CME). Methods: This was a nested case-control study. All adult patients who underwent cataract surgery between January 1, 2006 and December 31, 2016 and who were enrolled in the PharMetrics Plus database were eligible for inclusion. The association between postoperative topical PGAs (bimatoprost, latanoprost, and travoprost/travoprost-z) or beta-blocker (betaxolol, levobunolol, and timolol) use and the incidence of pseudophakic CME was assessed by conditional logistic regression. Results: Five hundred eight cases and 5080 controls were included in the analyses. Incidence of pseudophakic CME was found to be statistically significantly associated with the current postoperative use of both topical PGAs [relative risk (RR), 1.86; 95% confidence interval (CI), 1.04-3.32] and topical beta-blockers (RR, 2.64; 95% CI, 1.08-6.49). Postoperative use of each of bimatoprost (RR, 2.73; 95% CI, 1.35%-5.53%) and travoprost/travoprost-z (RR, 3.16; 95% CI, 1.42-7.03) in the year before diagnosis was demonstrated to be statistically significantly associated with the incidence of pseudophakic CME. This association was not observed to be statistically significant with the postoperative use of latanoprost (RR, 1.55; 95% CI, 0.84-2.88). Conclusions: To the best of our knowledge this is the largest study that has investigated the association between postoperative topical PGA or topical beta-blocker use and the incidence of pseudophakic CME. Postoperative use of both topical PGAs and topical beta-blockers was found to be associated with the incidence of pseudophakic CME.